ECONOMIC HARDSHIP AS A PREDICTOR OF INTENTION TO QUIT AMONG ENTREPRENEURS IN EBONYI STATE, NIGERIA (IJOVTECH, 2026)
The increasing economic hardship in Nigeria has presented various businesses with high levels of distress that might exacerbate the intention to exit the business. The primary purpose of the present paper was to examine the intention to quit a business based on economic hardship. Although much has been written on the challenges of SMEs in Nigeria, this study explored whether economic hardship can predict the intention to quit. Data were sourced through a self-report instrument from 114 owners of SMEs in Ebonyi state, Nigeria. These were analyzed using simple regression analysis. The result indicated that economic hardship significantly predicted intention to quit at β = .924, p< .05. Most importantly, an observation of the R2 indicated that economic hardship as a variable contributed about 12.8% of the variation in the intention to exit.